Agroindustry Development Strategy for Capture Fisheries Rokan Hilir District - Arief, Hazmi; Yanti, Chicka Willy; Metalisa, Rindi (Faculty of Fisheries and Marine, Universitas Riau, 2023)
The fisheries sector has a very important role for the people in Rokan Hilir Regency in driving their economy. Therefore, the fishery potential that is owned must be utilized as much as possible for the welfare of the community. This research was conducted in March 2022. The method used is the survey method. This study aims to analyze the superior marine fishery agroindustry products in Rokan Hilir Regency and determine the internal and external factors of the marine capture fisheries agroindustry as well as alternative strategies for developing marine capture fisheries agroindustry in Rokan Hilir District. The results of the AHP analysis showed that the results of the weighting and scoring of several types of commodities and post-harvest technology used were known that the superior marine fishery agroindustry products in Rokan Hilir Regency were processed products derived from shrimp raw materials. While the results of the SWOT analysis concluded that the position of the marine fisheries agroindustry in Rokan Hilir Regency based on the IE matrix was in cell V of growth and stability, which means that the position of the marine fisheries agroindustry was in a balanced position. Alternative strategies that can be applied are utilizing the availability of fish raw materials from nature, increasing support and attention to marine fisheries agroindustry businesses, improving & maintaining the quality of marine fisheries agroindustry products, proposing related training on financial managerial capabilities, establishing fisheries institutions/cooperatives marketing fisheries agroindustrial products sea, increasing more intensive training in pest and disease management, establishing partnerships with collectors/agents/traders so that production results are guaranteed price levels in marketing, establishing modern processing sites based on raw material handling so that the availability of raw materials can be stocked or stored to minimize costs production.